ANALYSIS OF THE IMPLEMENTATION OF SPECIFIC NUTRITIONAL INTERVENTION PROGRAMS AND SENSITIVE NUTRITIONAL INTERVENTIONS IN REDUCING THE INCIDENCE OF STUNTING IN TODDLERS IN PADANGSIDIMPUAN CITY - Normayanti Rambe; Lisna Khairani Nasution (Fakultas Kesehatan Masyarakat Institut Kesehatan Medistra Lubuk Pakam, 2022)
Padangsidimpuan City is an area with a high stunting prevalence rate in Padangsidimpuan City, including areas with a high stunting prevalence rate in 2019, and is included in the stunting prevention area. The prevalence of stunting in Padangsidimpuan City based on data from PK21 BKKBN is 23.11%. Specific nutritional interventions are part of the health sector and contribute 30 percent to solving the problem of stunting. The purpose of this study is to identify factors that influence the implementation of specific and sensitive nutritional intervention programs in reducing the incidence of stunting in toddlers in Padangsidimpuan City using the Consolidation Framework Implementation Research (CFIR). The type of research in this study is qualitative research, using observation and interview methods. Informants in this study are part of the program implementers and field implementers. Deductive analysis of data into CFIR domains and constructions. The results showed that the thirty CFIR constructions analyzed can be seen that the implementation of specific and sensitive nutrition intervention programs in reducing stunting rates in toddlers in Padangsidimpuan City is classified as quite good, this is influenced by ten CFIR constructions that distinguish the implementation of programs in the agencies of each informant where six CFIR constructions distinguish the implementation of specific nutrition intervention programs that have strong influence and four CFIR constructions that have a not very strong influence on program implementation but are very impactful in seeing the implementation of the program. Suggestions that can be given are the allocation of village funds for the development of community nutrition, strengthening the role of cadres in disseminating information and detecting community nutrition related to stunted children, and collaborating with outside agencies or organizations that also focus on handling stunting.